TINJAUAN PTSL KOTA BATAM MENURUT MENTERI AGRARIA DAN TATA RUANG NOMOR 6 TAHUN 2018 - Novaldo Adam; Endang Suparsetyani (Reformasi Hukum Trisakti, 2023)
Land registration is an important element to develop a land registration system within the scope of simultaneous registration for all villages and sub-districts. Main questions are whether the implementation of complete systematic land registration program in Batam has been carried out as stipulated in the Regulation of the Minister of Agrarian and Spatial Planning/Head of BPN No. 6 of 2018, how is the implementation of the complete systematic land registration regulation policy in Batam and how is Batam Government's effort to reduce the difficulty of realizing the complete systematic land registration program. Theseresearch wield normative juridical method with analytical descriptive type. The results of the research on the implementation of complete systematic land registration program in Batam are implemented through 13 stages, same as the program policy in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 6 of 2018. PTSL certificates are issued systematically, or by requiring the owner of the result user to pay both the annual mandatory fee and the Implementation Fee. Conclusion, the solutions are community counseling, collaboration with local government, getting rid of old villages, BPHTB payment rules, and cooperation with stakeholders including the Batam government.